The ferromagnetic domain wall as a GMR trilayer - Allen, W; Gregg, J; Ounadjela, K; Viret, M; Hehn, M; Thompson, S; Coey, J (1997)
By exploiting the simplicity of a novel transport measurement on a ferromagnetic striped domain structure in a thin film of cobalt, we report the first direct observation of ferromagnetic domain wall scattering and what we believe to be the first clear indication of giant magnetoresistive effects (GMR) in a homogeneous magnetic system. A new model is proposed to describe these observations which highlights the crucial role played by electron spin precession in determining the electrical transport properties of magnetic interfaces.